2018
DOI: 10.1107/s2053229618010690
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of the ZrIV interaction with the carboxamide bond in a noncovalent complex between Hen Egg White Lysozyme and a Zr-substituted Keggin polyoxometalate

Abstract: The successful cocrystallization of the noncovalent complex formed between (Et2NH2)8[{α‐PW11O39Zr‐(μ‐OH)(H2O)}2]·7H2O Keggin polyoxometalate (2) and Hen Egg White Lysozyme (HEWL) protein is reported. The resulting structural model revealed interaction between monomeric [Zr(PW11O39)]4−(1), which is a postulated catalytically active species, and the protein in two positions in the asymmetric unit. The first position (occupancy 36%) confirms the previously observed binding sites on the protein surface, whereas th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 44 publications
3
24
2
Order By: Relevance
“…The estimated molecular mass of the bands on the SDS-Tricine-PAGE gel and the results obtained from Edman degradation unambiguously conrmed that at pH ¼ 5.0 Hb was hydrolyzed at seven peptide bonds (Table S1 and occur via interactions between the substituted metal and the side chain of amino acids. [24][25][26]45,46 Fig. 7 shows that all hydrolyzed Asp-X bonds are present near the accessible surface of the protein and in the vicinity of the positively charged regions of Hb, which is consistent with the more efficient hydrolysis observed at lower pH, as decreasing pH leads to protonation of side chains in some amino acid residues.…”
Section: Selectivity Of Hemoglobin Hydrolysis By Ce IV Ksupporting
confidence: 71%
“…The estimated molecular mass of the bands on the SDS-Tricine-PAGE gel and the results obtained from Edman degradation unambiguously conrmed that at pH ¼ 5.0 Hb was hydrolyzed at seven peptide bonds (Table S1 and occur via interactions between the substituted metal and the side chain of amino acids. [24][25][26]45,46 Fig. 7 shows that all hydrolyzed Asp-X bonds are present near the accessible surface of the protein and in the vicinity of the positively charged regions of Hb, which is consistent with the more efficient hydrolysis observed at lower pH, as decreasing pH leads to protonation of side chains in some amino acid residues.…”
Section: Selectivity Of Hemoglobin Hydrolysis By Ce IV Ksupporting
confidence: 71%
“…Figure2Bs hows a selected snapshot with representative interactions between the oxygen atoms of POMf ramework and the amino acids of HEWL. As it had been computationally characterized [30] ande xperimentally observed, [31][32][33] the nature of thesei nteractions comprises mainly electrostatic interactions, hydrogen bonding and water-mediated interactions with positively-charged and polar amino acids.…”
Section: Influence Of the Pom Chargementioning
confidence: 99%
“…In this regard, computational modelling would allow performing systematic variations on single parameters of well-defined POM structuresa nd thus making possible this type of fundamental studies. In ap revious contribution, we provided ac omputational, atomistic description of the POM-protein interactions based on molecular dynamics simulations (MD) [30] The study was backed by experimentally reported systemsf ormed by model hen egg-white lysozyme (HEWL) protein and experimentally reported Ce IV -a nd Zr IV -sub-stitutedP OMs, [31][32][33] as well as, Te VI -centered POM. [34] Simulation revealed that POMs interact mainly with the side chains of the positivelyc harged and polar uncharged residues via chargea ttraction and hydrogen bonding of the basic oxygen atoms of POM framework.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Zr-substituted POMs have shown high affinity towards hydrolysis of peptide bonds next to amino acids with carboxylate groups in their side chains such as Asp and Glu residues [ 9 , 14 , 31 , 32 , 33 ]. The interactions between the negatively charged POMs and proteins typically occurs at positively charged areas on the protein surface, however in some cases POMs can also interact with amino acids via covalent binding [ 24 , 34 ]. Since the interactions between POMs and proteins depend on different factors such as size, shape, charge, and hydrophilicity of the POM the challenge is to understand how these factors influence the specificity and selectivity of protein hydrolysis.…”
Section: Introductionmentioning
confidence: 99%